P PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN SEKOLAH DASAR: PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN SEKOLAH DASAR - Rika Maharani; Sumianto; Afriza Rahma Rani; Yenni Fitra Surya; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' learning activeness through the implementation of the Project Based Learning (PjBL) model in IPAS learning for fifth-grade students at UPT SD Negeri 009 Bangkinang. This research employed Classroom Action Research (CAR), which was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 18 fifth-grade students. Data collection techniques included observation, documentation, and field notes. The research instrument used was an observation sheet of students' learning activeness. Data were analyzed using descriptive qualitative analysis by comparing students' learning activeness results in each cycle. The results of the study indicate that the implementation of the Project Based Learning (PjBL) model can improve students' learning activeness in IPAS learning. This improvement is evidenced by increased student participation in group discussions, collaboration in completing projects, courage in expressing opinions, and active involvement in all stages of the learning process. In Cycle I, students' learning activeness showed an improvement compared to the pre-action condition, while in Cycle II, students' learning activeness increased more significantly and met the predetermined success indicators. Based on these findings, it can be concluded that the Project Based Learning (PjBL) model is effective in improving the learning activeness of fifth-grade students in IPAS learning at UPT SD Negeri 009 Bangkinang.